Performance simulation of polymer-based nanoparticle and void dispersed photonic structures for radiative cooling - Bijarniya, Jay Prakash (Sci Rep, 2021)
Passive radiative cooling is an emerging field and needs further development of material. Hence, the computational approach needs to establish for effective metamaterial design before fabrication. The finite difference time domain (FDTD) method is a promising numerical strategy to study electromagnetic interaction with the material. Here, we simulate using the FDTD method and report the behavior of various nanoparticles (SiO(2), TiO(2), Si(3)N(4)) and void dispersed polymers for the solar and thermal infrared spectrums. We propose the algorithm to simulate the surface emissive properties of various material nanostructures in both solar and thermal infrared spectrums, followed by cooling performance estimation. It is indeed found out that staggered and randomly distributed nanoparticle reflects efficiently in the solar radiation spectrum, become highly reflective for thin slab and emits efficiently in the atmospheric window (8–13 µm) over the parallel arrangement with slight variation. Higher slab thickness and concentration yield better reflectivity in the solar spectrum. SiO(2)-nanopores in a polymer, Si(3)N(4) and TiO(2) with/without voids in polymer efficiently achieve above 97% reflection in the solar spectrum and exhibits substrate independent radiative cooling properties. SiO(2) and polymer combination alone is unable to reflect as desired in the solar spectrum and need a highly reflective substrate like silver.